EFEKTIVITAS DAN KESADARAN MASYARAKAT PADA PENGELOLAAN BANK SAMPAH INDUK BUNCU ELHa DI KABUPATEN HULU SUNGAI UTARA - Jakaria Jakaria; Emmy Sri Mahreda; Syarifuddin Kadir; Rizqi Puteri Mahyudin (Universitas Lambung Mangkurat, 2026)
Waste management remains one of the major environmental challenges faced by many countries, including Indonesia, as population growth and increasing human activities escalate the volume and diversity of waste generated. Community-based initiatives such as waste banks play a strategic role in supporting the 3R (reduce, reuse, recycle) principle and promoting circular economy practices. This study aims to analyze the effectiveness of the Buncu ELHa Central Waste Bank Program and the level of public awareness regarding waste management in Hulu Sungai Utara Regency. The research was conducted from September to October 2025 using qualitative and quantitative approaches, with data collected through observations, interviews, questionnaires, and documentation. Effectiveness was measured using a Likert-scale descriptive percentage method, while public awareness was assessed using a scoring technique. The results show that the effectiveness of the Buncu ELHa Central Waste Bank Program is categorized as very effective, with an average score of 81.77%, indicating optimal operational performance in waste sorting, collection, recording, and recycling processes. Community awareness also falls under the very aware category, with an average score of 82.07%, reflecting strong participation in waste sorting, saving, and information dissemination. Although the program’s contribution to the total managed waste volume remains relatively small (15.29 tons/year or 4.52% of total managed waste), it demonstrates positive behavioral changes and supports community empowerment in environmental management. The findings highlight the importance of strengthening institutional capacity, increasing socialization efforts, and enhancing supporting facilities to improve regional waste management performance.